Hormone-receptor interactions are noncooperative: application to the beta-adrenergic receptor. - Pollet, R J (1980)
We have developed kinetic methods with which we have demonstrated that the negatively cooperative hormone-binding model is untenable for the insulin receptor system. These methods have led others to the same conclusion for the thyrotropin and nerve growth factor receptors. We report here the application of these methods to the study of (l)-[propyl-2,3-3H]dihydroalprenolol [(l)-[3H]DHA] binding at 15 degrees C to the beta-adrenergic receptor of the frog erythrocyte--the remaining and most extensively characterized hormone receptor-cyclase system in which negatively cooperative site-site interactions have been reported. Scatchard analysis of the equilibrium binding data for (l)-[3H]DHA in this system is linear. In addition, increasing concentrations of (l)-[3H]DHA during the binding reactions resulted in increasing receptor occupancy but no enhancement of the subsequent dilution-induced dissociation of bound hormone, demonstrating directly that the dissociation rate is independent of occupancy. Furthermore, analysis of the time course of the approach-to-equilibrium for this system at different hormone concentrations was consistent with reversible hormone binding to a homogeneous class of noncooperative receptors, and the analysis yielded a kinetically estimated equilibrium constant consistent with that derived from the linear equilibrium data. The above data indicate that negatively cooperative site-site interactions are not a significant factor for the beta-adrenergic receptor of the frog erythrocyte. These results complete the demonstration that for all known hormone receptor systems, the hormone binds noncooperatively to one or more classes of independent receptor sites. The need for critical reinterpretation of detailed thermodynamic, clinical, and hormone analogue studies based on the negative cooperativity model is discussed.